Elements of the informal economy in the tourism - Mekhovych, K. S.; Pererva, P. G. (My University, 2023)
It is proven that in the structure of the informal economy proposed by the authors, we deliberately focus only on the market structural elements of the informal economy (shadow and criminal). Enterprises, firms and organizations of the market informal economy are functional backups of those operating in the conditions of the formal economy, which, as we noted above, act either contrary to the current legislation in the market sphere or outside it.
Елементи неформальної економіки на туристичному ринку
Keywords: tourist market; demand; supply; informal relations; shadow income